GRAPH TANGGA DAN SIFAT-SIFATNYA - LARASATI, MARETA SEKAR; HARINI, LUH PUTU IDA; SUMARJAYA, I WAYAN (E-Jurnal Matematika; Vol 12 No 3 (2023), 2023)
Ladder Graph is one type of connected and simple graph that has its own uniqueness. The aim of this research is to find the k-deficiency of points in the spanning tree in the ladder graph. Calculation of k-deficiency is carried out for each additional step, starting from the second ladder ( L 2 ), up to the n th  Ladder (L n ). Calculations are based on a representative spanning tree on each ladder. In the end, we get a number pattern from the second ladder onwards which is then proven by mathematical induction, for the calculation of each step up the ladder.   In this   study, the pattern of k-deficiency points on the ladder graph was obtained.